2018
DOI: 10.1177/1479972318785832
|View full text |Cite
|
Sign up to set email alerts
|

The influence of South Asian ethnicity on the incremental shuttle walk test in UK adults

Abstract: The objective of this study was to compare incremental shuttle walking test (ISWT) performance between South Asian and Caucasian British adults, identify predictors of ISWT distance and produce ethnicity-specific reference equations. Data from a mixed gender sample aged 40–75 years from Leicestershire, United Kingdom, were selected for analyses. Analysis of covariance determined differences in ISWT performance between South Asian and Caucasian British ethnic groups. Linear regressions identified predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, this study did not indicate how changes in these variables affected distance walked, and only reported that these factors begot significant differences; furthermore, these data were not disaggregated into female and male subsets. Ethnic background may also impact distance walked; Orme et al found that the ISWD of South Asian adults was significantly less than that of Caucasian British people (451 ± 143 vs. 575 ± 180 m, p < 0.001) [56]. Multiple factors including height and leg length, as dictated by genetic heritage, likely contribute to this result; several studies have attributed increased height to increased ISWD (p < 0.001) [48,[50][51][52].…”
Section: Pregnantmentioning
confidence: 99%
“…However, this study did not indicate how changes in these variables affected distance walked, and only reported that these factors begot significant differences; furthermore, these data were not disaggregated into female and male subsets. Ethnic background may also impact distance walked; Orme et al found that the ISWD of South Asian adults was significantly less than that of Caucasian British people (451 ± 143 vs. 575 ± 180 m, p < 0.001) [56]. Multiple factors including height and leg length, as dictated by genetic heritage, likely contribute to this result; several studies have attributed increased height to increased ISWD (p < 0.001) [48,[50][51][52].…”
Section: Pregnantmentioning
confidence: 99%